Oxaliplatin/capecitabine or carboplatin/paclitaxel-based preoperative chemoradiation for resectable oesophageal adenocarcinoma (NeoSCOPE): Long-term results of a randomised controlled trial. (August 2021) - Mukherjee, Somnath; Hurt, Christopher; Radhakrishna, Ganesh; Gwynne, Sarah; Bateman, Andrew; Gollins, Simon; Hawkins, Maria A.; Canham, Joanne; Grabsch, Heike I.; Falk, Stephen; Sharma, Ricky A.; Ray, Ruby; et al.
Abstract: Aim: This is the first randomised study to evaluate toxicity and survival outcomes of two neoadjuvant chemoradiotherapy (CRT) regimens for patients with localised oesophageal adenocarcinoma (OAC) or gastro-oesophageal junction (GOJ) adenocarcinoma. The initial results showed comparable toxicity between regimens and pathological complete response (pCR) rate favouring CarPacRT. Herein, we report survival, progression patterns, and long-term toxicity after a median follow-up of 40.7 months. Methods: NeoSCOPE was an open-label, UK multicentre, randomised, phase II trial. Eighty-five patients with resectable OAC or GOJ adenocarcinoma, ≥cT3 and/or ≥cN1 (TNM v7), suitable for neoadjuvant CRT, were recruited between October 2013 and February 2015. Patients were randomised to OxCapRT (oxaliplatin 85 mg/m 2 on Days 1, 15, and 29; capecitabine 625 mg/m 2 orally twice daily on days of radiotherapy [RT]) or CarPacRT (carboplatin AUC2; paclitaxel 50 mg/m 2 on Days 1, 8, 15, 22, and 29). RT dose was 45 Gy/25 fractions/5 weeks. Both arms received induction chemotherapy (two cycles oxaliplatin 130 mg/m 2 on Day 1, capecitabine 625 mg/m 2 orally twice daily on Days 1–21) before CRT. Surgery was performed 6–8 weeks after CRT. The primary end-point was pCR. Secondary end-points were toxicity, progression-free survival (PFS), overall survival (OS), and patterns of progression. Results: Eighty-five patients were recruited from 17 UK centres. The median OS was 41.7 months (95% confidence interval [CI] 19.6 to not reached) in the OxCapRT arm and was not reached in the CarPacRT arm (multivariable hazard ratio [HR] = 0.48, 95% CIs: 0.24–0.95, P = 0.035). The median PFS was 32.6 months (95% CIs: 17.1 to not reached) in the OxCapRT arm and was not reached in the CarPacRT arm (multivariable HR = 0.54, 95% CIs: 0.29–1.01, P = 0.053). In both arms, the distant progression was twice as common as locoregional progression. Conclusions: OS and PFS favoured neoadjuvant CarPacRT over OxCapRT. Distant was more common than locoregional progression; therefore, priority should be given to optimising the systemic treatment component. Clinical trial information: EudraCT Number: 2012-000640-10; ClinicalTrials.gov: NCT01843829. Highlights: Randomised study of neoadjuvant chemoradiotherapy for oesophageal adenocarcinoma. The median overall survival was significantly better with CarPacRT. Across both arms, the distant was more common than locoregional progression.